The short-run and long-run relationship between foreign direct investment, trade openness, workers’ remittances, foreign economic assistance and human capital on real gross domestic product for Pakistan - Khan, Waris (2020)
Economic growth is an essential factor for a country’s development. Pakistan is a politically unstable country which has been witnessing slow economic growth and rampant corruption. The country’s population has a low standard of living and poor education as well as healthcare system. Key economic indicators show that Pakistan has not been able to register strong Real Gross Domestic Product (“RGDP”) growth and attract high levels of Foreign Direct Investment (“FDI”). The country’s Trade Openness (“TO”) is high, however it has been suffering from an on-going trade deficit. Although, large inflows from Foreign Economic Assistance (“FEA”) and Workers’ Remittances (“WR”) were received, and the population is on a growing trend, yet it was still unable to register strong economic growth.